A REVIEW ON MULTIMODAL SPEAKER RECOGNITION - K, Khadar Nawas (Asian Journal of Pharmaceutical and Clinical Research, 2017)
A review on multimodal speaker recognition (SR) is being presented. For many decades the speaker recognition has been studied and still it has grabbed the interest of many researchers. Speaker recognition includes of two levels –system training and system testing. The robustness of the speaker recognition system depends on the training environment and testing environment as well as the quality of speech .Air conducted (AC) Speech is a source from which speaker is recognized by extracting the features. The performance of the speaker recognition system depends on AC speech. further to improve the robustness and accuracy of the SR system various other sources(Modals) like Throat Microphone ,Bone Conduction Microphone, array of microphones,Non Audible murmur, non auditory information like video are used in complementary with standard AC microphone. This paper is purely a review on SR and various complimentary modals.